Aesthetic Perception as an Axiological Problem - Katalynas, Antanas (Problemos, 1972)
The paper deals with the analysis of the aesthetic relation between subject and reality. The author notes some progress in overcoming one-sided gnoseological approach to aesthetic phenomena and analyses the deficiencies occurring in Marxist literature, i.e., the contemplative materialistic understanding of certain aspects of reflection tendency to gnoseological interpretation of axiological questions, etc. An attempt is made to reveal the dialectic interdependence between gnoseological and axiological problems of the aesthetic perception.